Phenol cauterization for ingrown toenails. - Ramsay, G (1986)
A new clinic was set up to deal with all toenail problems referred to a large general hospital. Ingrowing toenails were the commonest problem dealt with and phenol cauterization, either partial or complete, was the standard form of treatment. Over a 2-year period 1013 phenol cauterizations were carried out on 631 patients. After a minimum of 12 months follow-up, the recurrence rate was 2.96%. All recurrences were successfully treated by repeat phenol cauterization. We conclude that phenol cauterization should replace surgical ablation in the treatment of ingrown toenails.